IT Technology for Establishing Borders of Reserved Territories in the Conditions of Land Reform in Ukraine - Maksymenko , N. V.; Peresadko, V. A.; Sinna , O. I.; Klieshch , A. A.; Baskakova, L. V. (Man and Environment. Issues of Neoecology, 2021)
The existence of only a paper outline scheme in the National Nature Park Project does not allow to unambiguously interpret the boundaries of the object. Purpose. Development of technique for establishing the boundaries of protected areas. Methods. Cartographic using the ArcGIS geographic information system Results. The basic cartographic document for the study was a scanned map at a scale of 1:50 000 showing the boundaries of the Gomilshansky Forests National Park from the National Nature Park (NNP) Project. The main problem was the lack of elements of its mathematical basis on the map. The IT technology of geo-linking the scanned map of the park boundaries in the GIS environment includes the following actions: linking topographic map sheets at a scale of 1: 50,000 in the ArcGIS geographic information system, saving the relevant geo-linked, transformed copies of the image; visualization of digital geodata with geometry and coordinates of points of boundaries of forest areas (quarters); download the scanned map of the boundaries of the NNP from the Project of creation without geographical reference and perform the procedure of sequential addition of control points of reference; image transformation and saving the result in geotiff format. After that, a polygonal vector layer of * shp format was created and the park territory was digitized according to the NNP Project. The result of the research was a map of the boundaries of the Gomilshansky Forests National Park in geotiff format, geographically linked in the ArcGIS environment, as well as a vector layer of the National Park’s territory based on it. Conclusions. The use of the developed technology allows to determine the location of any land plots in relation to the national nature park, knowing their coordinates or uploading the Public Cadastral Map of Ukraine to the GIS project.